Impact of Humble Leadership on Employees’ Innovative in Guangxi, China - Tian, Ye; Khantanapha, Napaporn (วารสารนวัตกรรมการศึกษาและการวิจัย, 2026)
Humble leaders make employees’ perceive the humility of the leader through behavioral expressions, and this process shapes employees’ work attitudes and is an important consideration in the process of employees’ innovation. So, this research aims to 1. determine the effect of humble leadership, organizational support, and psychological empowerment on innovative behavior; 2. analyze whether psychological empowerment mediates the relationship between humble leadership and employees’ innovative behavior; and 3. analyze whether psychological empowerment mediates the relationship between organizational support and employees’ innovative behavior. The research result can conclude the discussion and recommendations. This study employed mixed research methods. The population in quantitative was managers working in Chinese enterprises in Guangxi by the 20-times rule with 12 dimensions derived from four variables. The sample size is 240 respondents. For a qualitative study of 10 key experts in employees’ innovative behavior, an interview was conducted, and convenient sampling was used to choose the respondents. The research tools were a questionnaire and interview. This study found that 1. humble leadership and organizational support positively and directly affected psychological empowerment, and psychological empowerment positively and directly affected innovative behavior. 2. The psychological empowerment mediates the relationship between humble leadership and employees’ innovative behavior; indirect effects,3. the psychological empowerment mediates the relationship between organizational support and employees’ innovative behavior; indirect effects. However, this study found many approaches and theories to improve employees’ innovative behavior.